Pouco para quem recebe, muito para quem paga? : Folha e Twitter debatem auxílio emergencial ao longo da crise - Guilherme Marques Rodrigues (2023)
During the COVID-19 pandemic, the implementation of restrictive measures to prevent the spread of the virus made it essential to create a income transfer program, the Auxílio Emergencial, which directly benefited more than 68 million Brazilian families. Initially planned to last only 3 months, the Auxílio became the object of successive political decisions, involving both the periods of validity and the values of the benefits. Several complex dilemmas had to be solved in a short time and in a context permeated by uncertainties: a crisis that was at the same time sanitary, social, political and economic. With this in mind, our research investigates how the public debate on the Auxílio Emergencial developed throughout these processes of political decision that mobilized politicians, experts, journalists, activists and ordinary citizens. In light of the theoretical framework of deliberation and deliberative system, we will analyze the actors, themes and positions in 3 environments: contents published by Folha de São Paulo and disseminated on its Twitter, the comment section of @folha on Twitter and the comment section on Folha’s website. In addition to investigating the configuration of the public debate in these spaces throughout the decision-making processes, we also perform statistical analyses to examine the association between Folha’s texts and headlines and comments from subscribers and Twitter users, taking into account that the first group has full access to the contents and the second is limited by the paywall and can only see the headlines. We conclude with a discussion centered on Bolsonaro’s government and how it positioned itself in front of the dilemma between maintaining the payments of the benefits in the midst of a historical crisis or cutting them and sticking to its austerity project. The methodology used consisted of content analysis, being our units of analysis the paragraphs in Folha’s texts and comments from subscribers of the newspaper and Twitter users.